A Case Study of the Impact of Overweight on Body Image and Self-Esteem in a Population of Moroccan Adolescents and Adults (Indian Journal of Public Health Research & Development, 2020)
Context: According to WHO, obesity or overweight are risk factors of psychological disorders and qualityof life deterioration.Objective: Evaluating the impact of overweight on body image and self-esteem in a population of Moroccanadolescents and adults.Method: The study was carried out on 288 subjects (150 men, and 138 women), aged on average 34,86±0,82years [15 -76]. Over weight was measure dusing the Body Mass Index (BMI), body image was evaluatedusing the Physical Appearance Comparison Scale (PACS), and self-esteem was evaluated using theRosenberg Self-Esteem Scale (RSES).Results: 43,28 % (n= 103) of subjects had a normal body weight, 25,63% (n=61) were overweight and16,81% (n=40) were obese. 66,67% (68/102) of over weight subjects reported having compared theirphysical appearance to others. However, 60,46 % (78/129) of thosewith normal BMI also reported havingcompared their appearance to others some times or often. Among obese subjects, 73,68% (42/57) tend tocompare their physical appearance to others some times or often. In terms of self-esteem, 85,3% (n=209)have a low to verylow self-esteem, 13,1% (n=32) have a moderate self-esteem and 1.6% have a high selfesteem.However, only 15,13% (28/185) of subjects with normal BMI had a moderate to high self-esteem.A negative correlation was found between PACS and RSES (r= -0,139) and statistically significantcorrelations were found between BMI and both PACS (r= +0.125) and RSES (r= -0.189).Conclusion: Consequently, it is recommended to establish multi-disciplinary programs for management ofover weight among adolescents and adults, to mainstream the care received and reduce the pressure theyexperience.
Keywords: Obesity, BMI, Body Image, Self-esteem, Prevalence, Morocco